(untitled) (Research, Society and Development, 2022)
The objective of this study is to propose a model for the strategic management of a technological incubator of popular cooperatives. This is research of qualitative nature, classifying itself in as much as the purposes are concerned as being prescriptive since it promotes solutions and direct replies to the problem presented, or may yet prescribe an ideal theoretical model to delimit concepts. The results of a field research were used, in which a semi-structured interview was used, since the interviews revealed a lack of literature on strategic management in ITCP. The research interviewees were the coordinators of the technological incubators of popular cooperatives in the state of Paraíba. This resulted in a model for strategic management of ITCPs divided into six stages, which are: participative management model; ITCP environment; participative planning; strategy formulation; strategy implementation; and control and evaluation. The proposed model is structured through the primordial factors of the solidarity economy, as well as the obstacles that ITCPs face in elaborating and implementing strategic planning, and how to strategically manage the incubated enterprises. In this way, the model developed intends to channel the efforts adopted by the ITCP with the incubated enterprises, demystifying the obstacles listed by the ITCP’s and with the diversity of the incubated enterprises, considering the incubation criteria that best fit the incubated ones.